Sculpture of Vishnu-016 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Vishnu is holding Shankha and Chakra in the upper two hands. Lower right hand has a mace and the left hand is empty.